Pengaruh Retribusi Dan Pajak Daerah Terhadap Pendapatan Asli Daerah Di Kabupaten Badung Tahun 2017 – 2021 - Ni Kadek Puspita Dewi; I Made Endra Lesmana Putra (Hita Akuntansi dan Keuangan, 2023)
This research was conducted to learn how Badung Regency's regional taxes and regional levies affect the region's budget. The tests of normality, correlation, multicollinearity, heteroscedasticity, and multiple linear regression used here are all part of the more traditional statistical methodology. During the period from 2017 to 2021, a total of 180 samples will be collected. This will include 60 samples of Regional Original Income, 60 samples of levies, and 60 samples of regional taxes. As a result, we found: The Regional Original Income in Badung Regency increases significantly as a result of retribution. This outcome suggests that Regional Original Income in Badung Regency would rise along with the increase in levies. Badung Regency's Regional Original Income benefits significantly from regional taxes. These findings imply that the administration of Badung Regency might expect a larger share of the Regional Original Income if the Regional Tax in that region is raised to greater levels.